Needs assessment of the public health curriculum based on the first-level health services package in Isfahan University of Medical Sciences - Pari Moradi; Athar Omid; Nikoo Yamani (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: After graduation, public health students should be able to work as health care givers providing first-level health care services. Therefore, the educational objectives of public health bachelor's programs should ensure that they acquire the capabilities necessary for this purpose. This study identified the educational objectives that are essential for these students and compared them with the current curriculum in Isfahan, Iran. METHODS: This needs assessment study was conducted in two phases. In the first phase, the essential educational objectives were identified using a qualitative approach, which involved eight focus group discussions held by a group consisting of experts of the public health headquarters and public health network administration offices of Isfahan province and the public health graduates working in the province's comprehensive health service centers, who were chosen using the purposive sampling method (n = 59). In the second phase, a comparative study was performed by turning the list of essential educational objectives into a checklist and using it to compare these objectives with the objectives in the current course plan in the examined curriculum. In the end, a list of educational objectives not included in the current curriculum of the public health bachelor's program was created. RESULTS: The focus group discussions produced 433 educational objectives in the cognitive domain, 79 objectives in the affective domain, and 179 objectives in the psychomotor domain, which were arranged in eight competency categories. Comparison of the essential educational objectives with the current curriculum showed that the current curriculum does not cover any of the essential objectives regarding care for the age groups of 18-29 and 30-59 and the first aid and only partially covers essential objectives in other competency categories. CONCLUSION: This study found that considering the requirements of first-level health services and the tasks expected from public health graduates to be providing these services, the current curriculum does not cover all essential learning objectives and should be revised to meet additional essential educational objectives.